2012
DOI: 10.1371/journal.pone.0032672
|View full text |Cite
|
Sign up to set email alerts
|

Protease Activity Increases in Plasma, Peritoneal Fluid, and Vital Organs after Hemorrhagic Shock in Rats

Abstract: Hemorrhagic shock (HS) is a major cause of death after trauma. During HS, perfusion to the intestine and pancreas are reduced, resulting in increased intestinal mucosal permeability, pancreatitis, and potential leakage of serine proteases (i.e. trypsin‐a potent matrix metalloproteinase [MMP] activator) into the circulation. We hypothesize that after HS, both trypsin and MMP‐9 enter the circulation, peritoneal space, and appear in peripheral organs. Male Wistar rats were grouped into No‐HS or HS (N=5). Mean art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 35 publications
5
39
0
Order By: Relevance
“…In particular: i) the controlled procedure for blood withdrawal and return (executed at the same rate of 0.5 cc/min, as explained in the Materials and Methods) is completely reproducible; ii) the objective control of the hemodynamic state of the animal during hypovolemia is ensured by the maintenance of blood pressure around the target value of 35 mmHg; iii) the monitoring of conditions such as body temperature (decreased following bleeding, constant throughout the hypovolemic phase, and increased again to physiologic levels upon reperfusion) is conveniently repeatable. All these elements are consistently observed in our experience with this HS model [35, 25]. Of particular benefit for proteomics/peptidomics studies is this particular model minimizes trauma to the animals (e.g., a laparotomy was not done), mitigating the potential for confounders to the analysis of hemorrhage per se.…”
Section: Discussionmentioning
confidence: 60%
“…In particular: i) the controlled procedure for blood withdrawal and return (executed at the same rate of 0.5 cc/min, as explained in the Materials and Methods) is completely reproducible; ii) the objective control of the hemodynamic state of the animal during hypovolemia is ensured by the maintenance of blood pressure around the target value of 35 mmHg; iii) the monitoring of conditions such as body temperature (decreased following bleeding, constant throughout the hypovolemic phase, and increased again to physiologic levels upon reperfusion) is conveniently repeatable. All these elements are consistently observed in our experience with this HS model [35, 25]. Of particular benefit for proteomics/peptidomics studies is this particular model minimizes trauma to the animals (e.g., a laparotomy was not done), mitigating the potential for confounders to the analysis of hemorrhage per se.…”
Section: Discussionmentioning
confidence: 60%
“…They may be further carried into venous blood vessels and intestinal lymphatics, and even across the full thickness of the small intestine directly into the peritoneal cavity (2527). The escape of pancreatic proteases from the small intestine is accompanied by an increase in digestive protease activity in plasma and tissues, such as the liver, lung and heart (25,27), suggesting that endogenous inhibitors of digestive proteases may become fully bound and their ability to block proteases has become saturated (2830). In experimental shock, proteases circulate in plasma and exhibit elevated activities as detected by cleavage of fluorescently quenched substrates (27,31), irrespective of whether caused by a directly ischemic state (e.g.…”
Section: Entry Of Digestive Enzymes Into the Systemic Circulationmentioning
confidence: 99%
“…MMPs can increase endothelial and epithelial permeability by proteolytic cleavage of the ectodomain of junctional proteins and opening of intercellular junctions (25,37,38), increasing mucosal permeability early in shock. MMPs also have the ability to digest the basement membrane of endothelium (39), thereby allowing characteristic tissue lesion formation due to escape of plasma and blood cells into the surrounding tissue (27).…”
Section: Matrix Metalloproteinases – Trigger For Elevated Permeabilitymentioning
confidence: 99%
“…This is a primary theory underlying the pathogenesis of the inflammatory cascades induced by heat stroke (8,25) and hemorrhagic shock (51). However, recent studies have demonstrated that other inflammatory mediators besides endotoxin cross the intestinal barrier and may be equally, if not more, important in initiating proinflammatory cascades and MODS (1,2,18,20,50). The most promising of these is one or more naturally occurring pancreatic digestive enzymes (20,50).…”
Section: B Heat Strokementioning
confidence: 99%